2022
DOI: 10.1080/0886022x.2022.2049306
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a break-in period of less than 24 hours for urgent start peritoneal dialysis: a multicenter study

Abstract: Purpose Urgent start peritoneal dialysis (USPD) is an effective therapeutic method for end-stage renal disease (ESRD). However, whether it is safe to initiate peritoneal dialysis (PD) within 24 h unclear. We examined the short-term outcomes of a break-in period (BI) of 24 h for patients undergoing USPD. Methods This real-world, multicenter, retrospective cohort study evaluated USPD patients from five centers from January 2013 to August 2020. Patients were divided into B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…In this study, laparoscopic surgery did not increase the operative time, time from operation to starting PD and time from operation to discharge, which would not affect patient management. Although guidelines recommend a break-in period of at least 2 weeks before PD starts, starting USPD within 2 weeks after catheter insertion has no major influence on catheter-related complications [ 19 ]. To minimize the risk of leakage, these patients started automated PD in the supine position with a small-volume PD prescription.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, laparoscopic surgery did not increase the operative time, time from operation to starting PD and time from operation to discharge, which would not affect patient management. Although guidelines recommend a break-in period of at least 2 weeks before PD starts, starting USPD within 2 weeks after catheter insertion has no major influence on catheter-related complications [ 19 ]. To minimize the risk of leakage, these patients started automated PD in the supine position with a small-volume PD prescription.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, percutaneous catheterization was more and more widely used in USPD. A real-world, multicenter, retrospective cohort study found percutaneous catheterization was more commonly used for a break interval <24 h and laparoscopic or open surgery method was more commonly used for a break interval >7 days [ 22 ]. Another study compared percutaneous with surgical implantation in USPD [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…We followed this commonly used definition of urgent-start PD (who require dialysis initiation less than 2 weeks) [7,[28][29][30][31] when we conducted this study. However, several recent published data reported their successful experience of urgent-start PD with less than 72-h break-in period [32][33][34][35][36], which we did not take it into consideration. Therefore, further exploration are needed to verify the feasibility of urgent-start PD less than 72 h. It is a single center, self-matched design, which limits the generalizability of the results.…”
Section: Discussionmentioning
confidence: 99%